Palm-based business development at Al Hidayah Islamic Boarding School in Sei Mencirim Village, Kutalimbaru Sub-District, Deli Serdang District - Elisa Julianti; R.B. Moh. Ibrahim Fathoni; T. Irmansyah; Muhammad Setiawan; Intan Mustika Sari; Afflia Putri Salsabilla (Journal of Saintech Transfer, 2025)
educational institution that offers free education to its students. Its operational funding is supported by a business unit that processes palm sap into molded palm sugar, liquid palm sugar, palm sugar crystals, and other palm-based products such as candied palm fruit. However, the production methods used are still traditional and depend on simple tools, which often lead to variations in product quality. This community service program was designed to enhance productivity and improve the quality of palm sap products through the introduction of modern processing technology. The program consisted of seven phases: socialization, preparation of tools and materials, training, provision of equipment and technology, technology implementation, mentoring and evaluation, and ensuring sustainability. Participants included pesantren leaders, teachers, and students. The technologies introduced such as sap cooking machines, drying ovens, and sieving equipment—significantly improved efficiency. The sap cooking machine reduced processing time to about 2 hours, compared to the traditional 4–6 hours. The resulting molded, liquid, and crystal palm sugar products exhibited better and more consistent quality. Participants have also gained the necessary knowledge and skills to apply these innovations independently.